2020
DOI: 10.3390/cells9041033
|View full text |Cite
|
Sign up to set email alerts
|

Insights into P-Glycoprotein Inhibitors: New Inducers of Immunogenic Cell Death

Abstract: Doxorubicin is a strong inducer of immunogenic cell death (ICD), but it is ineffective in P-glycoprotein (Pgp)-expressing cells. Indeed, Pgp effluxes doxorubicin and impairs the immunesensitizing functions of calreticulin (CRT), an “eat-me” signal mediating ICD. It is unknown if classical Pgp inhibitors, designed to reverse chemoresistance, may restore ICD. We addressed this question by using Pgp-expressing cancer cells, treated with Tariquidar, a clinically approved Pgp inhibitor, and R-3 compound, a N,N-bis(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 46 publications
0
18
1
Order By: Relevance
“…In overcoming P-glycoprotein (P-gp)-expressing doxorubicin resistance in breast cancer cells, the clinically approved P-gp inhibitor tariquidar and its derivatives restored doxorubicin accumulation and enhanced ICD, defined as an increase in CRT translocation and the release of HMGB1 and ATP [ 94 ]. Thus, pharmacological compounds that abolish drug resistance may act as chemosensitizers and immunosensitizers, increasing the therapeutic effect.…”
Section: Roles Of Damps and Icd In The Clinical Significance Of Breast Cancermentioning
confidence: 99%
“…In overcoming P-glycoprotein (P-gp)-expressing doxorubicin resistance in breast cancer cells, the clinically approved P-gp inhibitor tariquidar and its derivatives restored doxorubicin accumulation and enhanced ICD, defined as an increase in CRT translocation and the release of HMGB1 and ATP [ 94 ]. Thus, pharmacological compounds that abolish drug resistance may act as chemosensitizers and immunosensitizers, increasing the therapeutic effect.…”
Section: Roles Of Damps and Icd In The Clinical Significance Of Breast Cancermentioning
confidence: 99%
“…The difference of doxorubicin concentration between the two series, expressed as nmol doxorubicin extruded/min/mg cell protein was plotted versus the initial drugs’ concentration. Values were fitted to Michaelis‐Menten equation to calculate Vmax and Km, using the Enzfitter software (Biosoft Corporation, Cambridge, United Kingdom) [47] …”
Section: Methodsmentioning
confidence: 99%
“…The past three generations of p-gp inhibitors/modulators have not proven to be very successful due to low therapeutic index, presumably because of expression in several tissue types. However, a recent study has shown that inhibitors reducing both the amount and activity of p-gp are effective chemo-immmunesensitising agents ( Kopecka et al, 2020 ). P-gp also has similar effects on drug concentration within the brain.…”
Section: Transportersmentioning
confidence: 99%